Comparison of DNA vaccines with AS03 as an adjuvant and an mRNA vaccine against SARS-CoV-2 - Praveen Neeli; Dafei Chai; Xu Wang; Navid Sobhani; George Udeani; Yong Li (iScience, 2023)
Summary: Emerging variants of SARS-CoV-2 call for frequent changes in vaccine antigens. Nucleic acid-based vaccination strategies are superior as the coding sequences can be easily altered with little impact on downstream production. mRNA vaccines, including variant-specific boosters, are approved for SARS-CoV-2. Here, we tested the efficacy of DNA vaccines against the SARS-CoV-2 Spike aided by the AS03 adjuvant using electroporation and compared their immunogenicity with an approved mRNA vaccine (mRNA-1273). DNA vaccination elicited robust humoral and cellular immune responses in C57BL/6 mice with Spike-specific antibody neutralization and T cells produced from 20 μg DNA vaccines similar to that from 0.5 μg mRNA-1273. Furthermore, a Nanoplasmid-based vector further increased the immunogenicity. Our results indicate that adjuvants are critical to the efficacy of DNA vaccines in stimulating robust immune responses against Spike, highlighting the feasibility of plasmid DNA as a rapid nucleic acid-based vaccine approach against SARS-CoV-2 and other emerging infectious diseases.